Study of Morbidity and Mortality Pattern of Children Admitted in Paediatric Intensive Care Unit of Tertiary Care Children’s Hospital - Joshi, Prakash; Agrawal, Sumit; Sah, Umesh Prasad (Journal of Nepal Paediatric Society, 2020)
Introduction: Intensive care is predominantly concerned with the management of patients with acute life threatening conditions in a specialised unit. The objective of this study was to describe the morbidity and mortality patterns as well as outcome of patients admitted in the Paediatric Intensive Care Unit (PICU) of a tertiary care government paediatric hospital in Nepal. Methods: A cross-sectional study of 652 children admitted to the PICU of Kanti Children’s Hospital was undertaken from 1st January 2018 to 31st December 2018. The data were retrieved retrospectively from the record files of PICU regarding patient’s age, sex, inhabitant, admitting and final diagnosis, length of stay in the ICU and final outcome. Data were entered into MS Excel and analysed using Pearson’s Chi Square Test. Results: Among 652 admitted children between 1 month to 14 years of age, 397 (61%) were males and 255 (39%) females with male to female ratio 1.55:1. Majority 352 (54%) of them were in the age group of one month to 12 months of age. Pneumonia (216, 33.1%) was the major disease seen followed by septicemia (123, 18.9%), bronchiolitis (44, 6.7%), Other infectious diseases (38, 5.8%) and so on. Out of total admission, 484 (74.23%) cases improved, 46 (7.05%) left against medical advice (LAMA) and 120 cases died with mortality rate of 18.46%. More than half of the deaths (n = 87/120, 72.5%) were due to infections (Septicemia, acute gastroenteritis, pneumonia and meningitis and other infectious diseases). Conclusions: Pneumonia with respiratory distress was the major cause of PICU admission while fatality was highest for acute leukemia. Therefore it seems justifiable to improve primary and secondary health care facilities for timely and reliable delivery of current standardised therapeutic practice as well as to increase ICU facilities in those areas.